Unidad de capacitación y tecnificación agrícola (2019)
The previously presented project is generated from a regional analysis that arises, this generating some problems about the region from the city of Bogotá to the municipality of flanders in which the proposal for a partial plan would be carried out. Based on the problems analyzed, a project is proposed to help improve the productive vocation of the region, which was agricultural, which leads us to consider the agricultural training and technification unit, as with this project, education coverage is generated publishes of the region reducing the rates of emigration of young people to other cities to access a technical and technological program